2021
DOI: 10.1007/s10792-021-01768-3
|View full text |Cite
|
Sign up to set email alerts
|

The morphology of choroidal neovascularization in chronic central serous chorioretinopathy presenting with flat, irregular pigment epithelium detachment

Abstract: Purpose To evaluate morphological characteristics of choroidal neovascularization in chronic central serous chorioretinopathy (CSC) presenting with flat and irregular pigment epithelium detachment (FIPED) by means of innovative multimodal imaging. Methods In this observational cross-sectional study, we examined 10 consecutive patients affected by chronic CSC and FIPED using fluorescein angiography (FA), indocyanine-green angiography (ICGA) and optical cohe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…It was suggested that the morphology pattern of MNV observed by OCTA may be useful to distinguish the activity grade of type 1 MNV and be responsive to PDT or anti-VEGF agent. 5,6 However, no association between MNV pattern and clinical outcome was unclear in this study; a study with larger cases is needed. In this study, the mean area of MNV increased significantly (3-fold increase) after half-dose PDT in the eyes with definite MNV at baseline.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…It was suggested that the morphology pattern of MNV observed by OCTA may be useful to distinguish the activity grade of type 1 MNV and be responsive to PDT or anti-VEGF agent. 5,6 However, no association between MNV pattern and clinical outcome was unclear in this study; a study with larger cases is needed. In this study, the mean area of MNV increased significantly (3-fold increase) after half-dose PDT in the eyes with definite MNV at baseline.…”
Section: Discussionmentioning
confidence: 74%
“…Type 1 MNV is considered to be the most common type that occurs in pachychoroid disease, 2,4 and its morphology has been noted to include "pruned tree pattern" and "tangled pattern" defined as follows: pruned tree pattern, filamentous vessels with a main neovascular trunk and a few branches, and tangled pattern, filamentous vessels with a thick net and wool-like appearance. 5 PCV characterized by polypoidal lesion may also be associated with pachychoroid disease. 2,4 In addition, a thicker choroid is a characteristic of CSC, suggesting that cases with MNV have a thinner choroid than those without MNV.…”
mentioning
confidence: 99%
“…This finding signifies the role of OCTA in detecting the vascular complex under SIPEDs. However, the presence of MNV in SIPED has been reported at rates ranging from 24 to 95% [22][23][24][25][26][27] ; this discrepancy could be related to the absence of well-defined criteria.…”
Section: Discussionmentioning
confidence: 96%